TERJERAT KASUS KORUPSI KOMISI AGEN - Irwan, Sayid (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2017)
The aim of this research is to know the corruption as an extraordinary crime .The method is based on library through magazine and regulation No 31 the year 1999 , has been revised by the regulation No. 20 in the year 2001 on the combat of corruption and at  once  the  Book  of  Regulation  Crime  Act  (  KUHP)  namely  join  to  do  the corruption.The results of the research are (1).Corruption is difficult to find out it is , therefore , taking a long time to detect,(2).The proof tools have to be strong by calling the seewaitness,(3).The Regulation of the Corruption act is complete ,(4).The activity which needs budget has to be factually done, (5).Corruption must have to enrichen himself or herself and others,(6).The KPK staffs are very patient and inteligent.The suggestins are(1).KPK staffs have to be patient ,countable and calm ,(2).The proof tools have to be valid ,(3).Every officer has to study the regulation completely and seriously the regulation,(4).No fictive ativity ,(5).Every officer has to avoid to enrichen himself and others,(6).The KPK fficers continue to improve their performance.